2008
DOI: 10.1021/jm701583b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Promiscuous Small Molecule Activators in High-Throughput Enzyme Activation Screens

Abstract: It is recognized that high-throughput enzyme inhibition screens often return nonspecific inhibitors as "hits". Recently, high-throughput screens for enzyme activators have led to the identification of several compounds with novel and potent biological activity. Here, we show that enzyme activation screens can also uncover compounds that activate multiple enzymes in a nonspecific fashion. Described herein are the general structural features of such compounds and methods to differentiate between specific and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
1
27
1
Order By: Relevance
“…Compound 1 has reduced effectiveness at the highest enzyme concentration tested, so we further investigated potential non-specific effects by testing it against unrelated enzymes. While general mechanisms for non-specific activation have not been thoroughly investigated, it has been suggested that non-specific activators may act like detergents by interfering with adsorption of protein to surfaces [25]. If this were the mechanism for compound 1, or for our other hit compounds, then it should have similar effects on many other types of enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 1 has reduced effectiveness at the highest enzyme concentration tested, so we further investigated potential non-specific effects by testing it against unrelated enzymes. While general mechanisms for non-specific activation have not been thoroughly investigated, it has been suggested that non-specific activators may act like detergents by interfering with adsorption of protein to surfaces [25]. If this were the mechanism for compound 1, or for our other hit compounds, then it should have similar effects on many other types of enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…These values tracked closely the concentrations required for half-maximal effect on catalytic activity (EC 50 values)-7.1 and 7.2 μM for 2A2 and 1F8, respectively. None of the most activating or inhibiting disulfide fragments had a significant impact on the activity of wild-type PDK1 and all were approximately equally effective toward mutants in the absence and presence of the detergent CHAPS, which is known to disperse small molecule aggregates that can lead to spurious enzyme activation or inhibition (15)(16)(17) (Fig. 3B and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These aggregates are readily identified by diagnostic experiments, including detergent sensitivity, β-lactamase inhibition, and sensitivity to bovine serum albumin (BSA) 14-16 . Furthermore, others have reported that detergent sensitive molecules in screening libraries can also promote enzyme activity 17 . We performed these diagnostic tests on 1541 with mixed results.…”
mentioning
confidence: 99%